Clusters as a model of economic development of Serbia - Jugoslav Anicic; Svetlana Vukotic; Nebojsa Zakic; Marko Laketa; Luka Laketa (UTMS Journal of Economics, 2013)
Insufficient competitiveness of small and medium enterprises in Serbia can be significantly improved by a system of business associations through clusters, business incubators and technology parks. This connection contributes to the growth and development of not only the cluster members, but has a regional and national dimension as well because without it there is no significant breakthrough on the international market. The process of association of small and medium enterprises in clusters and other forms of interconnection in Serbia is far from the required and potential level.The awareness on the importance of clusters in a local economic development through contributions to the advancement of small and medium sized enterprises is not yet sufficiently mature. Support to associating into clusters and usage of their benefits after the model of highly developed countries is the basis for leading a successful economic policy and in Serbia there are all necessary prerequisites for it.
Keywords: O1; 330; clusters; small and medium enterprises; competitiveness; economic development